Edaravone Reduces Hyperperfusion-Related Neurological Deficits in Adult Moyamoya Disease: Historical Control Study. Issue 7 (July 2016) - Uchino, Haruto; Nakayama, Naoki; Kazumata, Ken; Kuroda, Satoshi; Houkin, Kiyohiro
Abstract : Background and Purpose—: Postoperative hyperperfusion-related transient neurological deficits (TNDs) are frequently observed in adult patients with moyamoya disease who undergo direct bypass procedures. The present study evaluated the effect of the free radical scavenger edaravone on postoperative hyperperfusion in adult moyamoya disease. Methods—: This study included 92 hemispheres in 72 adult patients who underwent direct bypass for moyamoya disease. Serial measurements of cerebral blood flow were conducted immediately after surgery and on postoperative days 2 and 7. In 40 hemispheres for 36 patients, edaravone (60 mg/d) was administered from the day of surgery to postsurgical day 7. The incidence of postoperative hyperperfusion and associated TNDs were compared with a control group that included 52 hemispheres in 36 patients. Results—: Radiological hyperperfusion was observed in 28 of 40 (70.0%) and 39 of 52 (75.0%) hemispheres in the edaravone and control groups, respectively ( P =0.30). Hyperperfusion-related TND incidences were significantly lower in the edaravone group compared with the control group (12.5% versus 32.7%; P =0.024). Multivariate analysis demonstrated that edaravone administration ( P =0.009) and left-sided surgery ( P =0.037) were significantly correlated with hyperperfusion-related TNDs (odds ratios, 0.3 and 4.2, respectively). Conclusions—: Perioperative administration of edaravone reduced the incidence of hyperperfusion-related TNDs after direct bypass procedures in adult patients with moyamoya disease.